Examining the Influence of ICT on the Teaching and Learning of Mathematics in Colleges of Education in Ghana: An Empirical Review - Kissi, Dora; Akyea, Seth Ntow; Ayete, Emmanuel Larbi; Kwarteng , Daniel (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This study examined the influence of information and communication technology  (ICT) on the pedagogy and acquisition of mathematical knowledge in colleges  of education in Ghana. The analysis of how information and communication  technology (ICT) is employed in the instruction and acquisition of mathematical  concepts is conducted through the utilisation of the Technological Pedagogical  Content Knowledge (TPACK) framework. The study employed a desktop study  methodology. The study emphasises the significance of educators having proficiency  in the three domains of Technological Pedagogical Content Knowledge (TPACK)  to successfully integrate technology into their teaching practises. The paper  additionally examines the strategies implemented by the Ghanaian government to  promote the incorporation of information and communication technology (ICT)  within educational establishments. The present study suggests that it is imperative  to provide fundamental information and communication technology (ICT)  resources, such as computers, laptops, and infrastructure, in order to facilitate the  successful incorporation of ICT into the educational process within Colleges of  Education in Ghana schools.
Keywords: ICT; Teaching; Learning Mathematics; Colleges of Education